2023
DOI: 10.1039/d3cc00718a
|View full text |Cite
|
Sign up to set email alerts
|

Lab-on-a-DNA origami: nanoengineered single-molecule platforms

Abstract: DNA nanotechnology holds great promise for development of a lab-on-a-DNA origami. We summarize the latest trends based on DNA origami focusing on light-harvesting nanoantennas and platforms for single-molecule optical spectroscopy and/or atomic force microscopy (AFM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…244,245 Another approach is to design complex architectures for single-molecule experiments. 246 One such architecture, the DNA origami frame developed by Endo et al was already demonstrated to be suitable for enzyme interaction studies. ( e.g.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…244,245 Another approach is to design complex architectures for single-molecule experiments. 246 One such architecture, the DNA origami frame developed by Endo et al was already demonstrated to be suitable for enzyme interaction studies. ( e.g.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…DNA origami nanostructures (DONs) are made by folding DNA single-stranded scaffolds to desired shapes using designed complementary staple strands [5]. Knowledge of all DNA pairs of the structure allows for precise positioning of DNA segments, nanoparticles or other molecules into advanced experimental configurations on a single DON [6]. In the present study, we focused on the stability of the nanostructure itself under illumination by UV light as a prerequisite to our radiation damage experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advancements in single-molecule (SM) SERS have undeniably ushered in a new era of molecular study . This innovative approach promises unparalleled insights into molecular systems, especially proteins.…”
mentioning
confidence: 99%
“…The recent advancements in single-molecule (SM) SERS have undeniably ushered in a new era of molecular study. 6 This innovative approach promises unparalleled insights into molecular systems, especially proteins. Through the merger of SM-SERS with gold nanopores, 7 the scientific community is presented with an opportunity to scrutinize individual protein segments in ways previously considered unattainable, offering the potential of SM protein sequencing.…”
mentioning
confidence: 99%